Pengaruh Budaya Organisasi, Motivasi Kerja, Kompetensi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Pegawai Kantor Pusat Perumdam Tirta Satria Purwokerto - Anza Saefal; P. Edi Sumantri; Arinastuti (ProBisnis : Jurnal Manajemen, 2026)
This study aims to examine the partial effects of organizational culture, work motivation, work competence, and work environment on employee job satisfaction at the Head Office of Perumdam Tirta Satria Purwokerto. The population consisted of 144 permanent employees, with 111 respondents selected using proportionate stratified random sampling. Data were analyzed using multiple linear regression with SPSS. The results show that all independent variables have a positive and significant effect on job satisfaction. The coefficient of determination (R²) of 0.696 indicates that 69.6% of the variation in job satisfaction is explained by the four variables, while 30.4% is influenced by other factors. The F-test confirms that the regression model is feasible. The findings imply that management should enhance attention to employees’ work-related issues, provide greater appreciation, ensure competency alignment through continuous training, and maintain work facilities to support effective job performance. Future research is recommended to broaden the sample scope and assist respondents during questionnaire completion.